Artisan entrepreneurs in Cairo and early-modern capitalism - Hanna, Nelly (Middle East studies beyond dominant paradigms., 2011)
Offering richly detailed portraits as well as an overview of the Ottoman Empire's economic landscape, Hanna incorporates artisans into the historical development of the period, portraying them in the context of their work, their families, and their social relations. These artisans developed a variety of capitalist practices, both as individuals and collectively in their guilds. Responding to the demands of expanding commercial environments in Egypt and Europe, artisans found ways to adapt both production techniques and the organization of production. Hanna details the ways in which artisans defied the constraints of the guilds and actively engaged in the markets of Europe, demonstrating how Egyptian artisan production was able to compete and survive in a landscape of growing European trade.